Bitcoin as an example of a virtual currency - Anna Wisniewska (Institute of Economic Research (IER), 2016)
Virtual currencies have recently become one of the most popular topics in the media. This paper focuses on economic aspects of Bitcoin, being an attempt to answer the question if Bitcoin can be considered money in the light of economic theories of money. On the basis of the reports published by the European Central Bank and the Financial Action Task Force, as well as the available Internet and primary sources, there have been presented the types, history and functioning of virtual currencies. The knowledge of virtual currencies makes it possible to foresee the problems arising from their existence, such as possible threats to international security, difficulties with taxation etc. The growing popularity of virtual currencies and cryptocurrencies is linked with the increase of importance of non-cash payments on global scale. Thus, Bitcoin may be considered next step in the evolution of digital money.
Keywords: E40; G29; G28; K34; 330; bitcoin; virtual currencies; cryptocurrencies; legal status of virtual currencies